A Candidate for True Type-2 AGN without Hidden Central Broad-line Regions Identified by Central Tidal Disruption Event - Ying Gu; Qi Zheng; Pei-zhen Cheng; Xiao Li; Xing-Qian Cheng; Xue-Guang Zhang; En-Wei Liang (The Astrophysical Journal)
In this manuscript, through applications of tidal disruption event (TDE) expected variability properties, a potential candidate for True Type-2 active galactic nuclei (TT2AGN) without hidden central broad-line regions (=TT2AGN) is reported in SDSS J233454.07+145712.9 (=SDSS J2334). Through analyzing the 20 yr optical light curves of SDSS J2334 from different Sky Survey projects, a TDE is preferred with a 4.7 M _⊙ main-sequence star tidally disrupted by the central black hole (BH) with mass 11.7 × 10 ^6 M _⊙ , indicating that central region within a distance of about 20 light days to the central BH in SDSS J2334 is directly in the line of sight. Moreover, active galactic nucleus (AGN) activities in SDSS J2334 can be confirmed through applications of (Baldwin, Phillips, & Terlevich (BPT) diagrams. Meanwhile, comparing virial BH mass determined through assumed broad Balmer emission components and M-sigma expected BH mass by well-measured stellar velocity dispersion through stellar absorption features, optical broad emission lines in SDSS J2334 are disfavored with confidence level higher than 6 σ . Therefore, combining the unique properties of the TDE and the spectroscopic results with only narrow emission lines, SDSS J2334 can be well identified as a potential candidate for a TT2AGN. The results indicate that to detect TDE expected flares in normal Type-2 AGN classified by spectroscopic results should be a new practicable method for identifying TT2AGN.